Marketing Strategy, Brand Image on Consumer Purchase Interest - Erni Rusyani (Budapest International Research and Critics University, 2022)
The purpose of this study is to examine the impact of marketing strategy and brand image on consumer interest in purchasing garments at the Quenza bella fashion Muslim shop. The study's demographic consists of all people aged 17 and above in Tasik City who have purchased Quenza bella fashion Muslim clothing, with a total of 39 respondents. Primary data is the sort of data used in this investigation. Data collection methods using a google form questionnaire. SmartPLS 3.0 is the analytical instrument that was utilized to test the hypothesis. The results of the study show that Brand image has an important positive influence on buying attention, sales strategy has an important positive influence on brand image, and sales strategy does not affect buying attention.